Extrabudgetary Funds - Radev, Dimitar (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note1 addresses the following main questions: 1. What are the definition, classification, and typology of extrabudgetary funds (EBFs)? 2. Why do EBFs exist? 3. What are the problems created by EBFs? 4. What are the criteria for evaluating and reforming EBFs? and 5. What are the implications for analysis of fiscal policies and for public financial management (PFM)?.